Acute poisoning in children admitted to pediatric emergency department: a five-years retrospective analysis - Soave, Paolo Maurizio; Curatola, Antonietta; Ferretti, Serena; Raitano, Vincenzo; Conti, Giorgio; Gatto, Antonio; Chiaretti, Antonio (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: to identify most frequent risk factors and to propose prevention strategies for the children admitted to Pediatric Emergency Department (PED) with acute poisoning. Methods: We performed a retrospective study in a tertiary care hospital, describing the frequency and nature of pediatric poisoning, clinical management and outcome. Results: We collected data of 436 children admitted for acute poisoning. The mean age was 30 months and 51.1% were male. Most poisoning incidents (90.1%) were unintentional and drug ingestion (39.4%) was the leading cause of poisoning. Acute poisoning happened at home in 83,7% of cases and the mother was the most frequent caregiver during the event in 61.5%. No died were reported. Conclusion: Our study showed that the two categories of patients at greatest risk for acute poisoning are children under 3 years and adolescents over 12 years. Adequate information campaigns about toxic substances are essential for children, adolescents and their parents.